A Protocol for the Pharmacokinetics of Enteric Coated Mycophenolate Sodium in Lupus Nephritis (POEMSLUN): an open-label, randomised controlled trial. Issue 8 (7th August 2013) - Ranganathan, Dwarakanathan; John, George T; Healy, Helen; Roberts, Matthew J; Fassett, Robert G; Lipman, Jeffrey; Kubler, Paul; Ungerer, Jacobus; McWhinney, Brett C; Lim, Aaron; Purvey, Megan; Reyaldeen, Reza; et al.
Abstract : Introduction: Mycophenolate sodium, an enteric-coated tablet (EC-MPS), is as effective and safe as mycophenolate mofetil (MMF) in preventing transplant rejection. EC-MPS and MMF improve the outcome of severe lupus nephritis (LN) and have fewer side effects than pulsed intravenous cyclophosphamide. Blood concentrations of mycophenolic acid (MPA), the active metabolite of EC-MPS, vary between participants despite fixed dosing. Interpatient variability has been studied in transplantation, but not well documented in LN. The relationship between MPA concentration and its clinical effect on LN has not been described. Methods and analysis: This is a prospective, open-label, randomised controlled trial. –32 participants with LN who meet the inclusion and exclusion criteria will be randomised into two groups: one receiving a fixed dose of EC-MPS and the second, a dosing regimen that is titrated with therapeutic drug monitoring. Included participants will have blood sampled over a period of 8–12 h on three different occasions. Pharmacokinetic parameters will be calculated using non-compartmental methods. Ethics and dissemination: The Human Research and Ethics Committee of the Royal Brisbane Women's Hospital have approved this study. The study is registered with Australian and New Zealand Clinical Trials Registry—ACTRN12611000798965 We planned to present the de-identified information at conferences and publish the results in medical journals. Trial Registration: ACTRN12611000798965